Mapping of the amniotic fluid proteome of fetuses with congenital anomalies of the kidney and urinary tract identifies plastin 3 as a protein involved in glomerular integrity. Issue 5 (16th June 2021) - Fédou, Camille; Camus, Mylène; Lescat, Ophélie; Feuillet, Guylène; Mueller, Ilka; Ross, Bryony; Buléon, Marie; Neau, Eric; Alves, Melinda; Goudounéche, Dominique; Breuil, Benjamin; Boizard, Franck; et al.
Abstract: Congenital anomalies of the kidney and the urinary tract (CAKUT) are the first cause of chronic kidney disease in childhood. Several genetic and environmental origins are associated with CAKUT, but most pathogenic pathways remain elusive. Considering the amniotic fluid (AF) composition as a proxy for fetal kidney development, we analyzed the AF proteome from non‐severe CAKUT ( n = 19), severe CAKUT ( n = 14), and healthy control ( n = 22) fetuses using LC–MS/MS. We identified 471 significant proteins that discriminated the three AF groups with 81% precision. Among them, eight proteins independent of gestational age (CSPG4, LMAN2, ENDOD1, ANGPTL2, PRSS8, NGFR, ROBO4, PLS3) were associated with both the presence and the severity of CAKUT. Among those, five were part of a protein–protein interaction network involving proteins previously identified as being potentially associated with CAKUT. The actin‐bundling protein PLS3 (plastin 3) was the only protein displaying a gradually increased AF abundance from control, via non‐severe, to severe CAKUT. Immunohistochemistry experiments showed that PLS3 was expressed in the human fetal as well as in both the fetal and the postnatal mouse kidney. In zebrafish embryos, depletion of PLS3 led to a general disruption of embryonic growth including reduced pronephros development. In postnatal Pls3 ‐knockout mice, kidneys were macroscopically normal, but the glomerular ultrastructure showed thickening of the basement membrane and fusion of podocyte foot processes. These structural changes were associated with albuminuria and decreased expression of podocyte markers including Wilms' tumor‐1 protein, nephrin, and podocalyxin. In conclusion, we provide the first map of the CAKUT AF proteome that will serve as a reference for future studies. Among the proteins strongly associated with CAKUT, PLS3 did surprisingly not specifically affect nephrogenesis but was found as a new contributor in the maintenance of normal kidney function, at least in part through the control of glomerular integrity. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.